2006
DOI: 10.1089/ten.2006.12.1821
|View full text |Cite
|
Sign up to set email alerts
|

In SituMonitoring of Tendon Structural Changes by Elastic Scattering Spectroscopy: Correlation with Changes in Collagen Fibril Diameter and Crimp

Abstract: The aim of this study was to monitor structural changes in loaded rabbit digital flexor tendons in situ and ex situ via elastic scattering spectroscopy (ESS). The optical setup consisted of a xenon white light source (lambda = 320-860 nm), connected to a fiber optic probe (with a source-detector separation of approximately 350 microm) and a spectrometer, controlled by a personal computer (PC). Cadaveric rabbit tendons were studied in situ under 3 tensional regimens: unloaded (no extrinsic tension applied), str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The observed decrease in mean fibril diameter corroborates an earlier study indicating smaller diameter fibrils in loaded tendons (Morgan et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed decrease in mean fibril diameter corroborates an earlier study indicating smaller diameter fibrils in loaded tendons (Morgan et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, we hypothesized that a multi-modal distribution of collagen fibril strains would be observed, and that this could be further related as a function of fibril diameter. Numerous authors (including ourselves) have conjectured that the bimodal distribution of large and small diameter fibrils may, respectively, enable load and creep resistance (Battaglia et al, 2003;Derwin and Soslowsky, 1999;Morgan et al, 2006;Rigozzi et al, 2010;Robinson et al, 2004b). This hypothesis was not born out by our data, which indicated that the collagen network stretches in a very uniform manner, both locally and across various anatomic tendon subregions, without obvious differences in mechanical strains between neighboring fibrils or between fibrils of different diameters.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It has been demonstrated to be capable of providing coarse optical sectioning, which can be useful in characterizing superficial tissue. [1][2][3][4] In addition, many tissue types are known to have polarization properties that affect the polarization state of light such as linear dichroism in sickled red blood cells, 5 linear birefringence in collagen, 6 and chiral rotation in glucose. 7 Noninvasively characterizing the polarization properties of tissues has potential for in vivo clinical applications, such as monitoring the healing state of wounds and burns.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Despite the importance of fibril diameter to the material properties of tissues, our basic understanding of its control is poor. Control of fibril diameter is distinct from fibrillogenesis, which is a thermodynamically driven aggregation following neutralisation of a native collagen solution.…”
Section: Introductionmentioning
confidence: 99%